(untitled) (Research, Society and Development, 2024)
Este artículo se refiere al uso de las Tecnologías de la Información y la Comunicación (TIC) en la enseñanza y el aprendizaje de la EJA en la Escuela Francisco Espinheiro Gomes, en el municipio de Castanhal, en el Estado de Pará. Objetivo: presentar los resultados de una investigación realizada en la Escuela Francisco Espinheiro Gomes, en Pará, sobre el uso de las TIC en la modalidad de EJA. Metodología: investigación de campo de carácter cuantitativo-cualitativo y enfoque descriptivo, seguida de una revisión bibliográfica en la Escuela Francisco Espinheiro Gomes, promoción de la 2ª etapa de la EJA. Results: 6 (six) EJA students, 2 (two) teachers participated and the technical staff had 1 (one) manager and 1 (one) coordinator. Conclusion: the reasons for the non-use of ICTs in the teaching and learning process in this school, it was found the lack of a direction from the management to be aligning the objectives of EJA with the development of actions that incorporate the practice of using ICTs as an accessible tool for communication and interaction between those involved, seeking the improvement of pedagogical practice, in breaking with the practice of traditional pedagogy in view of the fact that only 50% of EJA students have access to the use of ICTs.